2021
DOI: 10.18517/ijaseit.11.3.12733
|View full text |Cite
|
Sign up to set email alerts
|

Loads of Pollution to Lake Toba and Their Impacts

Abstract: Lakes provide various ecosystem services that support biotic habitats and human life. In contrast, many lakes in the world are degraded due to pollutant supply from surrounding areas and human activities in the lake. Lake Toba, which is the largest lake in Indonesia, has indicated a polluted condition. However, the source and load of each pollutant are not yet known. A study has been conducted to determine nutrient and organic load levels entering the lake represented by Total Phosphorus (TP) and Chemical Oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…Waters containing sufficiently high levels of phosphates, exceeding the normal needs of aquatic organisms, will cause eutrophication. High phosphate levels have a severe long-term effect on freshwater ecosystems and require significant efforts to reduce their concentration [19].…”
Section: Fig 7 Total Nitrogen Valuementioning
confidence: 99%
“…Waters containing sufficiently high levels of phosphates, exceeding the normal needs of aquatic organisms, will cause eutrophication. High phosphate levels have a severe long-term effect on freshwater ecosystems and require significant efforts to reduce their concentration [19].…”
Section: Fig 7 Total Nitrogen Valuementioning
confidence: 99%
“…Penelitian terdahulu mengungkapkan beberapa waduk di Indonesia telah tercemar. Penelitian (Lukman, 2021).…”
Section: Pendahuluanunclassified
“…Goodwin et al [23] investigated the formation of Lakes in Antarctica from Ocean flood events consisting from a mix of glacial meltwater and seawater. Lukman et al [24] studied the pollution in Lake Toba in Indonesia, where water quality at the lake was classified according to pollution status. Abd Aziz et al [25] identified water contamination in Cempaka Lake due to residential activities, clinics, restaurants and petrol stations.…”
Section: Introductionmentioning
confidence: 99%